Female Genital Mutilation as a Socio-Cultural Determinant of Infant and Maternal Mortality in Delta State - Elo-ghene Belin, RALPH-IMONIRUWE,; O. , Ogege, S.; Ejechi , Mrs. E. O. (Researchparks Publishing, 2023)
Female genital mutilation is still strongly supported and done in some communities in Delta State despite the campaign against it. This is because of the sociocultural factors that support this practise. Determinants of female genital mutilation in Delta State's rural and urban populations are therefore examined in this paper in terms of sociocultural factors. The study made use of cognitive dissonance theory. The use of both a questionnaire and an extensive interview schedule was part of a mixed technique study. Using the Yamane sample size calculation, 400 people were chosen as the study's sample. The study's participants were chosen using a multi-stage sampling technique. To test the study's hypotheses, the Pearson Product Moment Correlation method was employed. According to the study, female genital mutilation practise complicates childbirth for both mother and baby. This is due to poor hymen cutting, which makes it more likely for the mother and child to get infectious infections as a result and put their health at danger. According to the study, female genital mutilation should be discouraged through education and increased anti-mutilation campaigns.